1983
DOI: 10.1159/000265268
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Interaction in Visual-Evoked Responses: Summation, Facilitation and Inhibition in a Clinical Study of Binocular Vision

Abstract: Binocular visual-evoked responses (VER) were recorded in normal and strabismic subjects. The percent increase of binocular with respect to monocular response was correlated to the degree of binocular performance expressed by the values of stereopsis in the Titmus stereo test and TNO test. Summation, facilitation and inhibition of binocular responses were found. In no case was a clear relationship found between the degree of binocularity and the amplitude of binocular VER. This limits clinical application of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The results of earlier studies showed that binocular summation of VEPs in adults is less than that in infants [5,9,13,16]. In addition, the peak latency with binocular stimulation is shorter than that from monocular stimulation [1,2,8,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of earlier studies showed that binocular summation of VEPs in adults is less than that in infants [5,9,13,16]. In addition, the peak latency with binocular stimulation is shorter than that from monocular stimulation [1,2,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the peak latency with binocular stimulation is shorter than that from monocular stimulation [1,2,8,11]. It has been suggested that binocular enhancement is related to the presence of stereopsis [3,9,10,13,16], but other studies have found no relationship between binocular enhancement and stereopsis [5,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wright studied the primary visual cortex and used pattern VEPs in esotropes. Other studies showed normal or summated VEPs [2,14]. They found no clear relationship between the degree of binocularity and the amplitude of binocular VEP.…”
Section: Introductionmentioning
confidence: 90%